The Language of Donald Trump: The Discursive Construction of the EU’s Image in the President’s Public Statements - Ishpekova–Bratanova, Kalina; Mircheva, Mariana (Research Papers, 2020)
The present article aims to expose the role that the speech patterns of US President Donald Trump plays in the construction of his own political image as well as his stance on key issues pertaining to US foreign policy. It also makes a brief overview of the research on Trump’s speech patterns and discourse markers. A short analysis is made of the lexical, grammatical and stylistic perculiarities of his official statements on the EU and the relations between the United States and their European partners. The research is based on a range of the president’s media statements published in a number of English-language media outlets made during his tour across the EU and NATO, which reveal the limited vocabulary and imprecise grammar. The theoretical and methodological framework is interdisciplinary and includes political studies, the constructivist paradigm in the theories of international relations and some branches of modern linguistics. А special research interest are the discourse markers of Trump’s statements that are at once a linguistic element and an important component of social relations. The analysis shows Trump’s populist attitude as well as the rearranagment of some foreign policy priorities.